Characterization of Schizosaccharomyces pombe Copper Transporter Proteins in Meiotic and Sporulating Cells - Plante, Samuel (American Society for Biochemistry and Molecular Biology, 2014)
Meiosis requires copper to undertake its program in which haploid gametes are produced from diploid precursor cells. In Schizosaccharomyces pombe, copper is transported by three members of the copper transporter (Ctr) family, namely Ctr4, Ctr5, and Ctr6. Although central for sexual differentiation, very little is known about the expression profile, cellular localization, and physiological contribution of the Ctr proteins during meiosis. Analysis of gene expression of ctr4(+) and ctr5(+) revealed that they are primarily expressed in early meiosis under low copper conditions. In the case of ctr6(+), its expression is broader, being detected throughout the entire meiotic process with an increase during middle- and late-phase meiosis. Whereas the expression of ctr4(+) and ctr5(+) is exclusively dependent on the presence of Cuf1, ctr6(+) gene expression relies on two distinct regulators, Cuf1 and Mei4. Ctr4 and Ctr5 proteins co-localize at the plasma membrane shortly after meiotic induction, whereas Ctr6 is located on the membrane of vacuoles. After meiotic divisions, Ctr4 and Ctr5 disappear from the cell surface, whereas Ctr6 undergoes an intracellular re-location to co-localize with the forespore membrane. Under copper-limiting conditions, disruption of ctr4(+) and ctr6(+) results in altered SOD1 activity, whereas these mutant cells exhibit substantially decreased levels of CAO activity mostly in early- and middle-phase meiosis. Collectively, these results emphasize the notion that Ctr proteins exhibit differential expression, localization, and contribution in delivering copper to SOD1 and Cao1 proteins during meiosis.